MUNGBEAN (Vigna radiata) YI ELD AND DI-NITROGEN FIXATION UNDER MINIMUM TILLAGE AT SEMI ARID POTHWAR, PAKISTAN - S. Ali; A. Hasan; S. S. Ijaz; M. Ansar (Journal of Animal and Plant Sciences, 2013)
The field study was carried out during 2005 through 2007 at two locations (Rawalpindi and Fatehjang) in Pothwar, Pakistan to compare minimum tillage with conventional tillage practices for yield performance and nitrogen fixation in mungbean (Vigna radiata). The treatments including Minimum Tillage (MT), Conventional Cultivator (CC) and Moldboard Plow (MP) were laid out in a randomized complete block design. All the tillage treatments had equivalent profile moisture content at mungbean sowing. Consequently, the biomass and grain yields were also generally equivalent under all the tillage treatments. The average values were 3.10, 3.19, 3.64 Mg ha-1 for biomass and 0.59, 0.58, 0.60 Mg ha-1 for grain yield under MT, CC and MP respectively. The results on %Ndfa (nitrogen derived from atmosphere) and total N2-fixed varied with sites. At Rawalpindi site, though total nitrogen fixation slightly decreased with decrease in tillage intensity, the differences were statistically non significant. The average values were 24, 34, 32 percent for %Ndfa and 15, 19, 21 kg ha-1 for total N2-fixed under MT, CC and MP, respectively. At Fatehjang site, CC had significantly lower nitrogen fixation than MT and MP. The average values were 40, 12, 49 percent for %Ndfa and 24, 6, 32 kg ha-1 for total N2-fixed under MT, CC and MP, respectively. The results of study indicate that comparable mungbean grain yield and nitrogen fixation can be achieved by minimum tillage while avoiding current intensive tillage practices in semi arid Pothwar, Pakistan.
Keywords: legume; nitrogen fixation; yield; tillage; dry land